1993
DOI: 10.1257/jep.7.4.185
|View full text |Cite
|
Sign up to set email alerts
|

American and European Economics and Economists

Abstract: America and Europe differ with regard to what economics is understood to be, how it is practiced, and how professional academic economists behave. Specifically, 1) American (U.S. and Canadian) economists contribute by far the largest share of journal publications and are cited much more often than European economists, while (West-) European economists consider other aspects of their professional activities more relevant, in particular participating in local and national affairs; 2) economic research by America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 6 publications
2
69
0
3
Order By: Relevance
“…Finally, we have shown that European economic institutions are well behind their North-American counterparts in terms of economic research publications in the 10 leading economic journals considered. This finding raises concerns about the current state and impact of economic research in Europe relative to North-America and is in agreement with Frey and Eichenberger (1993) and Portes (1987). Providing a more thorough explanation of this phenomenon will be the subject matter of future research.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Finally, we have shown that European economic institutions are well behind their North-American counterparts in terms of economic research publications in the 10 leading economic journals considered. This finding raises concerns about the current state and impact of economic research in Europe relative to North-America and is in agreement with Frey and Eichenberger (1993) and Portes (1987). Providing a more thorough explanation of this phenomenon will be the subject matter of future research.…”
Section: Resultssupporting
confidence: 54%
“…Frey and Eichenberger (1993) provide some explanations, based on the different market conditions faced by U.S. and European economists. Table 3 reports the percentage of publication rates of North-American and European affiliations in each journal.…”
Section: The Share Of European Economicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Seção 4 discute explicações alternativas para a baixa publicação internacional dos brasileiros, e a Seção 5 conclui com uma discussão sobre os incentivos existentes no Brasil para a quantidade e qualidade de produção científica em Economia. Além de oferecer um ambiente propício à seleção dos melhores cérebros, Frey e Eichenberger (1992, 1993 argumentam que a mobilidade do mercado acadêmico americano e o processo de promoção de suas universidades cumprem um importante papel na construção da liderança em pesquisa dos EUA. As universidades americanas estão preocupadas não apenas com a quantidade da produção de seus pesquisadores, mas também com a sua qualidade.…”
Section: Introductionunclassified
“…The incentives to work in scientific advisory boards mainly consist in the reputation and a certain prominence gained. For persons who seriously embark on an academic career, these incentives are only weak or even negative (Frey and Eichenberger 1993, the special issue of Kyklos edited by R.L. Frey and B.S.…”
Section: Supplymentioning
confidence: 99%